Environmental Management of Lake Toba Tourism Area Indonesia - Indra Jaya (Budapest International Research and Critics University, 2019)
The objectives of this research was to know empirical information about the environment of Toba Lake tourism area as basis for building an alternative environmental management model. The research had been conducted at Lake Toba situated in North Sumatera. The research employed different steps i.e. survey, literature study, development of a conceptual model, validation of the model, preliminary test, evaluation and model revision, and finalization of the model developed. The results of the research indicated that the management of Lake Toba tourism must be improved and developed on the perspectives of sustainable environment and development